Long-Term Continuous Cervical Spinal Cord Stimulation Exerts Neuroprotective Effects in Experimental Parkinson’s Disease - Kuwahara, Ken; Sasaki, Tatsuya; Yasuhara, Takao; Kameda, Masahiro; Okazaki, Yosuke; Hosomoto, Kakeru; Kin, Ittetsu; Okazaki, Mihoko; Yabuno, Satoru; Kawauchi, Satoshi; Tomita, Yousuke; Umakoshi, Michiari; et al. (Frontiers in Aging Neuroscience, 2020)
Background Spinal cord stimulation (SCS) exerts neuroprotective effects in animal models of Parkinson’s disease (PD). Conventional stimulation techniques entail limited stimulation time and restricted movement of animals, warranting the need for optimizing the SCS regimen to address the progressive nature of the disease and to improve its clinical translation to PD patients. Objective Recognizing the limitations of conventional stimulation, we now investigated the effects of continuous SCS in freely moving parkinsonian rats. Methods We developed a small device that could deliver continuous SCS. At the start of the experiment, thirty female Sprague-Dawley rats received the dopamine-depleting neurotoxin, 6-hydroxydopamine, into the right striatum. The SCS device was fixed below the shoulder area of the back of the animal, and a line from this device was passed under the skin to an electrode that was then implanted epidurally over the dorsal column. The rats were divided into three groups: control, 8-h stimulation, and 24-h stimulation, and behaviorally tested then euthanized for immunohistochemical analysis. Results The 8-h and 24-h stimulation groups displayed significant behavioral improvement compared to the control group. Both SCS-stimulated groups exhibited significantly preserved tyrosine hydroxylase (TH)-positive fibers and neurons in the striatum and substantia nigra pars compacta, respectively, compared to the control group. Notably, the 24-h stimulation group showed significantly pronounced preservation of the striatal TH-positive fibers compared to the 8-h stimulation group. Moreover, the 24-h group demonstrated significantly reduced number of microglia in the striatum and SNc and increased laminin-positive area of the cerebral cortex compared to the control group. Conclusions This study demonstrated the behavioral and histological benefits of continuous SCS in a time-dependent manner in freely moving PD animals, possibly mediated by anti-inflammatory and angiogenic mechanisms.